Late Pleistocene - Holocene Sedimentary Evolution of Nam Bo Plain and Correlation from the Ca Mau Peninsula to the Mekong River Delta in Midle-Late Holocene - Trang, Nguyen Thi Huyen; Nghi, Tran; Thanh, Dinh Xuan; Thai, Nguyen Dinh; Nhan, Tran Thi Thanh (VNU Journal of Science: Earth and Environmental Sciences; Vol 35 No 4DO - 10.25073/2588-1094/vnuees.4476, 2019)
Located in southern Vietnam, the Southern plain is one of the largest in Asia. Within the coastal area, this study has indicated that there are two plains forming by different hydrodynamic mechanisms: the river dominated Mekong Delta plain and the tidal dominated plain of the Ca Mau peninsula. Studying lithofacies based on: (i) sedimentary parameters indicating environment of 29 boreholes in tidal flat and coastal plains, hundreds of surveyed surface sediment stations; (ii) stratigraphy seismic characteristics of the 21 seismic sections; and (iii) absolute age data, evolutionary history of late Pleistocene - Holocene sediments in the Southern plain and the relationship between the Mekong Delta and the tidal plain of the Ca Mau peninsula in the middle Holocene - late be clarified. Both plains are characterized by 3 lithofacies complexes corresponding to 3 phases of sea-level change: (i) lowstand alluvial facies complex (arLST Q 1 3b ); (ii) coastal facies complex (amtTST Q 2 1-2 ) and shallow marine-lagoon greenish-gray clay facies (mtTST Q 2 1-2 ); (iii) the phase of the middle-late Holocene (Q 2 2-3 HST) has a differentiation between the two plains. The Me Kong delta is characterized by three deltaic facies complexes: (1) the late middle-late Holocene buried submarine deltaic facies complex (amh 1 Q 2 2 - 3 ); (2) late Holocene deltaic plain facies complex (amh 2 Q 2 3 ) and modern submarine deltaic facies complex (amh 3 Q 2 3 ). The tidal plain of Ca Mau peninsula is characterized by a complex of sandy bars, tidal plains and tidal channels. In the regressive process, four periods of relative sea-level stopped, creating three ancient shoreline (5ka BP, 2.5ka BP; and 1 ka BP). The delta plain is marked by deltaic lobes turning to the southeast sea, while the Ca Mau plain characterized by the sand bars that tend to change direction from the east (2.5 ka BP) to the southeast (0.5ka BP and 0.2ka BP).